New Order And Solidarity Action In Facing Covid-19 (Students Experience) - Aniek Rahmaniah; Ulfi Andrian Sari (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
A key element in improving individual health is awareness of the risk of Covid-19, with in individuals to adjust to the new order. The purpose of this study is to find out how changes are felt by students in the presence of the Covid-19 pandemic. Using the phenomenological method, this research was conducted on the students of the Islamic State University Maulana Malik Ibrahim Malang. This study also wants to see the social changes felt by students and how students experience in the form of solidarity action. This research found that students showed self-awareness to start a new order, besides that social awareness also began to emerge, shown by their concern for the surrounding community. Some of the reasons that underlie the change in life towards this new order; rational considerations to participate in promoting healthy living and adhering to health protocols, religious values that they believe to help alleviate suffer in the surrounding community, their empathy for the impact caused by the Covid-19 pandemic.